Effects of B-vitamins on plasma homocysteine concentrations and on risk of cardiovascular disease and dementia. - Clarke, R; Lewington, S; Sherliker, P; Armitage, J (2007)
PURPOSE OF REVIEW: Dietary supplementation with folic acid and vitamin B12 lowers blood homocysteine concentrations, but it is not known if this reduces the risk of coronary heart disease and stroke. RECENT FINDINGS: Recent evidence suggests that the maximum reduction in plasma homocysteine concentrations is obtained with 0.8 mg of folic acid and doses of 0.2 mg and 0.4 mg of folic acid are associated with about 60 and 90%, respectively, of this maximal effect. Among 12 large trials (involving a total of 52,000 participants) that are currently assessing the effects of B-vitamins on risk of coronary heart disease and stroke, results are available for four trials involving 14 000 participants. A meta-analysis of these four trials demonstrates no beneficial effects of B-vitamins on coronary heart disease (OR 0.99; 95% CI 0.88-1.10) or stroke (OR 89; 95% CI 0.76-1.05) or the combination of coronary heart disease and stroke (OR 0.98; 95% CI 0.90-1.08). The confidence intervals around the odds ratios for these completed trials are compatible with a 10% difference in risk for coronary heart disease and 20% difference for stroke associated with a 25% lower homocysteine predicted by the observational epidemiological studies. SUMMARY: The results of the ongoing homocysteine-lowering trials are required before making recommendations on the use of B-vitamins for prevention of vascular disease.